Cationic Dye Adsorption Using Silica Xerogel from Corn Husk in A Continuous Fixed-Bed Column - Dahliyanti, Ayu; Nabila, Luthfia Jihan; Pratama, Arka Krisna; Widharyanti, Ika Dyah (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Silica xerogel from corn husks shows potential to be applied as an adsorbent for cationic dye removal due to its high adsorption capacity. However, the study regarding its performance in a continuous operation is still very limited, which hinders its application as a commercial adsorbent. To answer that problem, we investigate the adsorption of methylene blue (MB) and crystal violet (CV) dye using silica xerogel from corn husk in a continuous fixed-bed column. A breakthrough curve analysis was carried out with flow rate and bed height variations in an up-flow mode. The column effluent concentration was analyzed using a UV-Vis Spectrophotometer. The experimental data shows good agreement with the Thomas/Bohart-Adams and Yoon-Nelson model at different flow rates but has less correspondence for increasing bed height. Maximum adsorption capacities for methylene blue were 1.977 mg/g (Thomas/BA) and 1.743 mg/g (experimental). While for crystal violet the maximum adsorption capacities were 3.400 mg/g (Thomas/BA) and 4.573 mg/g (experimental). Keywords: adsorption, cationic dyes, silica xerogel, fixed-bed column, mathematical model.